Effects of 6 Weeks of Parenteral Cobalamin Supplementation on Clinical and Biochemical Variables in Cats with Gastrointestinal Disease. (12th September 2017) - Kempf, J.; Hersberger, M.; Melliger, R.H.; Reusch, C.E.; Kook, P.H.
Abstract : Background: Effects and duration of commonly used protocols for cobalamin (Cbl) supplementation on cellular Cbl deficiency have not been determined in hypocobalaminemic cats. Hypothesis/Objectives: To evaluate effect of Cbl supplementation on clinical signs, serum and urine methylmalonic acid (MMA) concentrations over 16 weeks. Animals: Twenty client‐owned hypocobalaminemic cats with enteropathy. Methods: Prospective study. Serum Cbl and serum and urine MMA concentrations were determined prospectively in cats at enrollment (t0), immediately before (t6), and 4 (t10) and 10 weeks (t16) after 6th Cbl injection (250 μg, IM q 7 days). Clinical signs severity (activity, appetite, vomiting, diarrhea, body weight) graded at each time point and expressed as clinical disease activity score. Results: Clinical disease activity score decreased during supplementation and increased after treatment discontinuation. Median serum Cbl concentration increased significantly from t0 (111 pmol/L, range 111–212) to t6 (2, 332.5 pmol/L, range 123–22, 730) ( P  <   0.01). Values at t10 were 610.5 pmol/L (range, 111–2, 527) and 180.5 pmol/L (range, 111–2, 262) at t16 ( P  <   0.01). Median baseline serum MMA concentration (372 μmol/L, range 0.39–147, 000) decreased significantly to 1.62 μmol/L (range, 0.18–806) at t6 ( P  <   0.01) and gradually increased to 5.34 μmol/L (range, 0.13–1, 730) at t10 and 189 μmol/L (range, 0.4–983) at t16. Similar, nonsignificant, pattern observed for urine MMA concentration. Serum and urine MMA concentrations had not normalized in 12 and 6 cats, respectively, at t6. Conclusion and Clinical Importance: The Cbl supplementation protocol used here did not lead to complete normalization of cellular Cbl deficiency in all examined cats, and biochemical improvements were transient.